Simply Charms : 20 Beading Projects - Published by Lark Carft (New York Lark Crafts, 2011)
On the catwalks of Europe, in cutting-edge boutiques, or adorning a celebrity's wrist, charm jewellery is the hottest accessory. From small photos encased in glass to flashy trinkets with Swarovski crystals to playful dice, dominoes, or jacks, this title presents various projects of charm jewellery.
Including Color Illustrations
Keywords: Charm bracelets -- Beadwork -- Charms (Ornaments)